2018
DOI: 10.1155/2018/3790760
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis and Monoclonal Gammopathy of Undetermined Significance (MGUS): A True Association or Just a Coincidence?

Abstract: Sarcoidosis is a systemic inflammatory disease characterized by the presence of noncaseating granulomas in different organs. Sarcoidosis associated with monoclonal gammopathy of undetermined significance (MGUS) is a rare finding with only 10 cases reported to date. We describe a 79-year-old male patient who presented with dry mouth for 4 months. Lip biopsy done prior to admission showed nonnecrotizing epithelioid cell granulomas. On admission, laboratory analysis was significant for elevated calcium, decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…For example, it has been reported that 11% of samples from patients with monoclonal gammopathy showed positive ANCA findings (19), while 6% of SjS patients were reported to have concomitant MGUS (20). Co-occurrence of sarcoidosis and MGUS has also been reported (21). Although there are no epidemiologic data to support the increased risk of MGUS in these systemic diseases, it has been suggested that dysregulation of the immune system may cause autonomous plasma cell clones and MGUS, while the dysregulation of cytokines, such as IL-1, IL-6, and TNF-α, may cause continuous stimulation of B cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that 11% of samples from patients with monoclonal gammopathy showed positive ANCA findings (19), while 6% of SjS patients were reported to have concomitant MGUS (20). Co-occurrence of sarcoidosis and MGUS has also been reported (21). Although there are no epidemiologic data to support the increased risk of MGUS in these systemic diseases, it has been suggested that dysregulation of the immune system may cause autonomous plasma cell clones and MGUS, while the dysregulation of cytokines, such as IL-1, IL-6, and TNF-α, may cause continuous stimulation of B cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of progression of MGUS to multiple myeloma is approximately 1% per year [1]. Although MGUS or multiple myeloma in association with sarcoidosis is not well elucidated, 10 such cases were previously reported [2,3]. Additionally, 33 cases with both sarcoidosis and multiple myeloma were also reported [4].…”
Section: Discussionmentioning
confidence: 99%
“…As the one side of sarcoidosis, lymphoproliferative neoplasm is known to occur concomitantly with sarcoidosis [5]. One explanation for the relationship between sarcoidosis and MGUS is that the hypergammaglobulinemia induced by the chronic inflammatory response with sarcoidosis results in prolonged plasma cell lifespan [2][3][4]. Due to the risk of progression to multiple myeloma, a careful follow-up is required.…”
Section: Discussionmentioning
confidence: 99%
“…Саркоидоз, связанный с моноклональной гаммапатией неопределенного значения (MGUS), является редким обнаружением -описано только 10 случаев, о которых известно в настоящее время [16]. В 30 % случаев саркоидоз был первоначальным диагнозом, и в 30 % -MGUS была первоначальным диагнозом.…”
Section: клинический случай §unclassified
“…Имеется ли истинная ассоциация между заболеваниями плазматической клетки и саркоидозом или это совпадение, должны определить большие проспективные исследования [17]. Длительное наблюдение за этими пациентами и контроль клинического анализа крови, электрофореза белков сыворотки крови и уровня креатинина позволит установить истину [16].…”
Section: клинический случай §unclassified